Insight into Metal–Organic Framework Reactivity: Chemical Water Oxidation Catalyzed by a [Ru(tpy)(dcbpy)(OH2)]2+‐Modified UiO‐67. Issue 2 (5th January 2018) - Lin, Shaoyang; Ravari, Alireza K.; Zhu, Jie; Usov, Pavel M.; Cai, Meng; Ahrenholtz, Spencer R.; Pushkar, Yulia; Morris, Amanda J.
Abstract: Investigation of chemical water oxidation was conducted on [Ru(tpy)(dcbpy)(OH2 )] 2+ (tpy=2, 2′:6′, 2′′‐terpyridine, dcbpy=5, 5′‐dicarboxy‐2, 2′‐bipyridine)‐doped UiO‐67 metal–organic framework (MOF). The MOF catalyst exhibited a single‐site reaction pathway with kinetic behavior similar to that of a homogeneous Ru complex. The reaction was first order with respect to both the concentration of the Ru catalyst and ceric ammonium nitrate (CAN), with k cat =3(±2)×10 −3  m −1  s −1 in HNO3 (pH 0.5). The common degradation pathways of ligand dissociation and dimerization were precluded by MOF incorporation, which led to sustained catalysis and greater reusability as opposed to the molecular catalyst in homogeneous solution. Lastly, at the same loading (ca. 97 nmol mg −1 ), samples of different particle sizes generated the same amount of oxygen (ca. 100 nmol), indicative of in‐MOF reactivity. The results suggest that the rate of redox‐hopping charge transport is sufficient to promote chemistry throughout the MOF particulates. Abstract : Hop to it : Water oxidation by [Ru(tpy)(dcbpy)(OH2 )] 2+ ‐doped UiO‐67 under chemical activation is demonstrated (tpy=2, 2′:6′, 2′′‐terpyridine, dcbpy=5, 5′‐dicarboxy‐2, 2′‐bipyridine). Results are consistent with a mononuclear mechanism and the metal–organic framework (MOF) is more stable than a molecular analogue. Evidence for facile redox hopping and in‐MOF reactivity is provided under chemical water‐oxidation conditions.